1993
DOI: 10.1227/00006123-199307000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Presentation of Symptomatic Subependymomas in Siblings

Abstract: Two young adult siblings independently developed similar neurological complaints that included headaches, photophobia, nausea, and intermittent lancinating facial pains. Magnetic resonance imaging revealed fourth ventricular lesions that required surgery in both patients. A pathological review revealed subependymomas with virtually identical histological features. The clinical features and common pathological findings of both patients suggest that familial subependymomas may have a maldevelopmental origin with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Since that time, more than 100 similar cases have been reported in the literature. With the exception of a very small number of cases that occurred in the brain parenchyma, cerebellopontine angle, and spinal cord, the overwhelming majority of these tumors have occurred within the fourth and lateral ventricles (2,5,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The true incidence of subependymomas is difficult to ascertain because many of the cases occurred in asymptomatic patients and were detected only incidentally at autopsy.…”
Section: Subependymomamentioning
confidence: 99%
See 1 more Smart Citation
“…Since that time, more than 100 similar cases have been reported in the literature. With the exception of a very small number of cases that occurred in the brain parenchyma, cerebellopontine angle, and spinal cord, the overwhelming majority of these tumors have occurred within the fourth and lateral ventricles (2,5,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The true incidence of subependymomas is difficult to ascertain because many of the cases occurred in asymptomatic patients and were detected only incidentally at autopsy.…”
Section: Subependymomamentioning
confidence: 99%
“…In a review of 1,000 serial necropsies in asymptomatic patients, Matsumura at al (17) reported the prevalence as 0.4%, compared with a prevalence of 0.7% in 1,000 consecutive craniotomies performed in symptomatic patients. Despite four case reports of subependymomas occurring in siblings, including one set of identical twins, no genetic susceptibility for the tumor has been proved (19,21,26).…”
Section: Subependymomamentioning
confidence: 99%
“…Less common sites include the third ventricle, the septum pellucidum and the spinal cord (16). In the vast majority of cases, they develop sporadically, though very occasional familial cases have been described (5, 6, 13, 30). One report describes infratentorial SE occurring in two identical twins (6).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few familial cases have been described. 3,4,8,19 The occurrence of subependymomas in identical twins supports the Cohnheim-Ribbert theory, which postulates that the persistence and subsequent dedifferentiation of multipotent embryonic cells can underlie tumor development. 4 However, presently we are still unable to answer the question of whether the origin is genetic or maldevelopmental.…”
Section: Discussionmentioning
confidence: 64%
“…2 To date, familial occurrence of subependymomas of the fourth ventricle has been reported only 4 times: twice in siblings, 3,8 in a father and his son, 19 and in identical twin brothers. 4 In this paper we report on the second case of subependymomas of the fourth ventricle in twin siblings.…”
mentioning
confidence: 99%